Deterioration and maintenance of pavements - Cudworth, David; Rahman, Mujib (ICE Publishing, 2023)
Deterioration and Maintenance of Pavements, Second edition is a hands-on guide and reference book that addresses the fundamental concepts of pavement analysis and design, deterioration mechanisms and asset management, and the practicalities in these areas. Now updated in this second edition and with additional information on pavement design principles, pavement deterioration, updated contents on design, investigation guidelines and asset management guidelines, this book covers the complete spectrum of pavement types, from footways to runways and from heavily trafficked roads in the UK to unpaved roads worldwide. Addressing specific practical issues including drainage and vehicle flow, and considering state-of-the-art data collection techniques for pavement evaluation, this book equips readers with the knowledge and tools to maintain a wide range of pavements.